Oncologic and Functional Outcomes of Partial Laryngeal Surgery for Intermediate‐Stage Laryngeal Cancer. Issue 2 (6th November 2012) - Caicedo‐Granados, Emiro; Beswick, Daniel M.; Christopoulos, Apostolos; Cunningham, Diana E.; Razfar, Ali; Ohr, James P.; Heron, Dwight E.; Ferris, Robert L.
Abstract : Objective: To evaluate the oncologic and functional outcomes of partial laryngeal surgery (PLS) using transoral laser microsurgery (TLM) and supracricoid laryngectomy (SCL) in patients with intermediate‐stage laryngeal squamous cell carcinoma (LSCC). Study Design: Historical cohort study. Setting: Single tertiary care center. Subjects and Methods: Retrospective review of oncologic and functional outcomes in intermediate‐stage (T2‐3/N0‐1, stage II and III) LSCC patients who underwent TLM or SCL from 1998 to 2010. Results: Sixty patients were included, of whom 28 (47%) underwent TLM and 32 (53%) underwent SCL. For the entire cohort, 2‐ and 5‐year probabilities were 86.2% (95% confidence interval [CI], 73.0%‐93.2%) and 72.9% (95% CI, 52.4%‐85.6%), respectively, for overall survival (OS) and 79.3% (95% CI, 65.6%‐88.0%) and 62.4% (95% CI, 41.9%‐77.4%), respectively, for recurrence‐free survival (RFS). There was no difference between the TLM and SCL cohorts in OS ( P =. 542) or RFS ( P =. 483). More than 75% of patients avoided adjuvant therapy. Communication Scale and Functional Outcome Swallowing Scale scores at median follow‐up of 33 months were 2 or better in 97% and 91% of patients, respectively, reflecting functional voice and swallowing postoperatively. Eighty‐eight percent of patients retained a functional larynx. Conclusion: PLS provides excellent oncologic and functional outcomes for intermediate‐stage LSCC and should be considered an alternative to chemoradiation or total laryngectomy in selected patients.